2022
DOI: 10.1186/s12905-022-01726-w
|View full text |Cite
|
Sign up to set email alerts
|

A case management model for patients with granulomatous mastitis: a prospective study

Abstract: Background Granulomatous mastitis (GM) is a chronic inflammatory mastitis disease that requires long-term treatment and has a high recurrence rate. Case management has been proven to be an effective mechanism in assisting patients with chronic illness to receive regular and targeted disease monitoring and health care service. The aim of this study was to investigate the application of a hospital-to-community model of case management for granulomatous mastitis and explore the related factors ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…The pathological changes of GLM center around the breast lobule, and its mechanism may be increased milk secretion followed by siltation to destroy the structure of breast lobules and ducts. Secretion overflow into the stroma can induce local immune reactions and lead to granuloma formation (53). A previous study (54) showed that there was a higher rate of breastfeeding in patients with GLM and that breastfeeding mothers took longer to relieve symptoms than those who did not breastfeed.…”
Section: Galactostasismentioning
confidence: 99%
“…The pathological changes of GLM center around the breast lobule, and its mechanism may be increased milk secretion followed by siltation to destroy the structure of breast lobules and ducts. Secretion overflow into the stroma can induce local immune reactions and lead to granuloma formation (53). A previous study (54) showed that there was a higher rate of breastfeeding in patients with GLM and that breastfeeding mothers took longer to relieve symptoms than those who did not breastfeed.…”
Section: Galactostasismentioning
confidence: 99%
“…It is a serious condition, since it clinically mimics cancer ( 6 ). Ethnic diversity has a role in the distribution of this condition, as GM occurrences are more prevalent in Middle Eastern nations compared to Western countries ( 7 ). GM in accessory breast tissue is rare.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, GM has become increasingly prevalent in China [ 6 ]. Its clinical presentation can be variable, ranging from acute infective episodes such as abscess or mastitis to breast lump resembling malignancy [ 5 , 7 , 8 ]. Sometimes, erythema nodosum and arthritis occur as extramammary presentations of GM [ 9 ].…”
Section: Introductionmentioning
confidence: 99%